Content Analyses of Scientific Articles from Issues Published in Sport Mont Journal in 2011 - Milos Kovacevic (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2018)
Sport Mont is scientific journal which uses contemporary methods with aim to present scientific knowledge to sport-conscious individuals. It is easily accessible with its printed and electronic edition, published three times a year by the Montenegrin Sport Academy (MSA), in February, June and October. Sport Mont functions as an open discussion forum on significant issues of current interest in fields of Sports Science and Medicine. It publishes original scientific papers, review papers, editorials, short reports, peer review - fair review, as well as invited papers and award papers. Sport Mont Journal covers wide range and Sport Science and Medicine. It includes all clinical aspects of exercise, health, and sport; exercise physiology and biophysical investigation of sports performance; sport biomechanics; sports nutrition; rehabilitation, physiotherapy; sports psychology; sport pedagogy, sport history, sport philosophy, sport sociology, sport management; and all aspects of scientific support of the sports coaches from the natural, social and humanistic side. This paper work it is about A Content Analysis of Published Articles in Sport Mont Journal in 2011. This paper work presents the table with titles of the scientific fields according to which the works were sorted and their exact number. In the subtitle, the results are all assigned to all the works that have been processed and, in the end, the subheading entitled discussion gives a brief overview of the results obtained. The aim of this paper work is to analyze the papers published in Sport Mont Journal in 2011. In such a way that all works will be selected according to the respective scientific fields to which they belong. This will allow easier search of the given source for all authors who, for some reason, serve the works published during this time period in Sport Mont.